2022
DOI: 10.1055/s-0042-1742682
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Pregnant Women with Bariatric Surgery History and Associated Factors

Abstract: Objective To analyze the prevalence and factors associated with depressive symptoms among Brazilian pregnant women with history of bariatric surgery (BS). Methods This is a cohort study with 247 women who got pregnant after BS. Based on data collection via Google Form, the recruitment of participants occurred in Facebook groups for 13 months. All of them answered a form with Informed Consent, a general data protocol and the Brazilian version of the Depression, Anxiety and Stress Scale-21. Descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Women with a history of BS are often afraid of weight regain during pregnancy, and their daily caloric intake is insufficient; therefore, it is crucial to provide them with specialist dietary and psychological care. The importance of psychological assistance is also important because depressive symptoms in pregnant women after BS affect approximately one-third of patients [22]. Hedderson et al presented a telephonic nutritional management program for pregnant women after BS.…”
Section: Dietary Supplementation In Pregnancies After Bariatric Surgerymentioning
confidence: 99%
“…Women with a history of BS are often afraid of weight regain during pregnancy, and their daily caloric intake is insufficient; therefore, it is crucial to provide them with specialist dietary and psychological care. The importance of psychological assistance is also important because depressive symptoms in pregnant women after BS affect approximately one-third of patients [22]. Hedderson et al presented a telephonic nutritional management program for pregnant women after BS.…”
Section: Dietary Supplementation In Pregnancies After Bariatric Surgerymentioning
confidence: 99%
“…Regardless of the type of bariatric surgery, reports concerning women's mental state during pregnancy are worrying. An increase in the incidence of mental disorders is reported, especially depression [88][89][90] and anxiety [89], as well as an increase in the incidence of self-harm and suicide [9], and a significant proportion of women who consume alcohol (33.5%) and use opioids (28.5%) have also been observed [90]. A significant relationship with depressive symptoms may include marital status, whether the pregnancy was planned and desired, and a history of mental disorders.…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%
“…In turn, mental disorders during pregnancy may increase the rates of abortion, hemorrhage, low birth weight, and negative consequences for the child's psychosocial development. In addition, the psychiatric background may result in less adherence to prenatal care and difficulties in the woman's acquisition of self-care habits, and it affects the quality of the mother-child relationship during pregnancy and postpartum, mainly due to its association with postpartum depression [88]. Considering the above facts, screening patients' mental condition after MBS is recommended before, during, and after pregnancy.…”
Section: The Influence Of Bariatric Surgery On Pregnancy and Neonatal...mentioning
confidence: 99%
“…These disorders can negatively impact fetal growth and development, leading to an increased risk of complications such as abortion or preterm labor [ 47 ]. It's crucial to assess and treat symptoms early to reduce negative consequences for maternal and child health [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, rapid changes may cause psychological disorders like depression, anxiety, alcoholism, and bulimia nervosa [ 59 ]. Pregnant women who had bariatric surgery are vulnerable to mental disorders during pregnancy, with depression/anxiety rates higher than those without surgery [ 50 ]. Furthermore, Kim et al reported that in the group of pregnant women with a history of bariatric surgery, the rate of depression/anxiety was 24.4%, while this rate was reported as 14.3% inpregnant women with obesity without a history of bariatric surgery [ 60 ].…”
Section: Introductionmentioning
confidence: 99%